04.19 3D synovial organoid culture reveals cellular mechanisms of tissue formation and inflammatory remodelling. (1st March 2017) - Calvo, Isabel Olmos; Byrne, Ruth A; Karonitsch, Thomas; Niederreiter, Birgit; Kartnig, Felix; Alasti, Farideh; Holinka, Johannes; Ertl, Peter; Kiener, Hans P
Abstract : Background: The synovial membrane is a distinctly organised tissue structure. During the course of rheumatoid arthritis (RA), the synovium becomes hyperplastic and demonstrates thickening of the lining layer and cellular condensation at the sublining layer. Using a three-dimensional synovial organ culture system, we explore cellular mechanisms of synovial tissue formation and inflammatory remodelling. Materials and methods: Fibroblast-like synoviocytes (FLS) derived from patients with RA were cultured in 3D micromasses. To mimic synovial inflammation, micromasses were challenged with TNF. For histological analyses, micromasses were embedded in paraffin, sections were stained with haematoxylin and eosin; Ki67 labelling was performed to identify proliferating cells. 3D confocal micrographs were analysed using Imaris Bitplane software. mRNA levels for various genes expressed in FLS were determined by qPCR. Results: Synovial micromasses demonstrated thickening of the lining layer over time. When stimulated with TNF, hyperplasia of the lining layer and cellular aggregation at the sublining layer was observed. In order to identify the origin of cells contributing to the thickening of the lining layer, proliferation studies were conducted. Intriguingly, in the early phase of the culture period, the percentage of proliferating cells in the lining layer was higher when compared to the sublining layer. This proliferative activity, however, was no longer present in the late phase, after the lining layer was established. In the presence of TNF, an increased number of proliferating cells at the lining layer was maintained for an extended period of time, consistent with higher rates of cellular proliferation at the synovial lining in sections of RA synovial tissues when compared to OA. qPCR data indicate that MMP1, MMP3, and IL-6 are differentially expressed during the early phase and the mature phase of the culture period. By contrast, lubricin, cadherin-11, CCL20, and STAT1 were not differentially expressed. Conclusions: The three-dimensional FLS micromass culture reveals spontaneous cellular organisation that strikingly resembles the lining/sublining architecture of the synovium. This process involves FLS proliferation as well as expression of genes that allow for tissue remodelling. In inflammatory conditions similar cellular programs are re-activated resulting in synovial lining hyperplasia and a pannus-like condensed mass of cells.